Analysis of Water Availability Potential to Support the Food Estate Program in Central Sumba Regency - Pentewati, Priseila; R Daniswara, Damian; Bees, Azarya; Santi L M F Seran, Sri (Fakultas Teknik, Universitas Brawijaya, 2026)
This study evaluates the potential of water resources to support the Food Estate (FE) program in Central Sumba, a semi-arid region in East Nusa Tenggara, Indonesia, where water scarcity and uneven distribution present major challenges for agricultural expansion. An integrative methodological framework was applied by combining dependable discharge analysis (Q80), calibrated satellite rainfall data, and multi-criteria prioritization using the Analytical Hierarchy Process (AHP). Calibration of GPM rainfall against ground observations improved input accuracy for hydrological modeling, while the Q80 analysis identified reliable sources, such as the Palamedo and Waiwakaka rivers and the Waikasoruk spring. Spatial prioritization revealed distinct zone characteristics: FE.1 as the core area with dependable flows, FE.2 as a buffer with moderate but seasonal resources requiring incremental interventions, and FE.3 as a resilience zone constrained by hard rock lithology, steep slopes, and high infiltration, demanding targeted measures such as catchment management and groundwater exploration. The findings provide practical policy guidance for staged Food Estate implementation, emphasizing small-scale infrastructure upgrades, adaptive water management, and zone-specific interventions that align with national food security objectives. While the framework proves effective in data-scarce environments, limitations remain in medium-term rainfall calibration and in limited discharge records, suggesting the need for future research on climate change impacts, long-term monitoring, and demand-supply scenario analysis.